A study of the saponins of Solanum torvum Sevilla (Fam. Solanaceae) - Robles, Yolanda Rodelas
The leaves of Solanum torvum Sevilla (Fam. Solanaceae) has been investigated for its saponin and sapogenin content. Isolation of the crude saponin was done using the general isolation procedure suggested by Wall, et al. using butanol as the extracting solvent. Thin-layer chromatography and column chromatography was employed to separate the components from each other. The Rf values was computed for the spots using different solvent systems. Attempt was also done to crystallize the crude sapogenins using large amount of ether. For the purpose of identification, infrared spectroscopy was employed.